Impact of Climate Change on Cropping Patterns and Farmer Adaptation Strategies: A Case Study in Tropical Regions - Muhammad Firdaus Adri; Messy Irawan; Nahri Idris (CV. HEI PUBLISHING INDONESIA, 2024)
Climate change has become a major focus in the agricultural context, especially in tropical regions where its impacts are felt more strongly. This study aims to investigate the impact of climate change on cropping patterns and farmer adaptation strategies in tropical regions, using a case study approach. The research method involves field surveys, interviews, and secondary data analysis to understand how climate change affects crop preferences, agricultural productivity, and farmer adaptation actions. The results show significant changes in cropping patterns and agricultural productivity in response to climate change, as well as various adaptation strategies implemented by farmers to address these challenges